2019
DOI: 10.1080/02635143.2019.1600490
|View full text |Cite
|
Sign up to set email alerts
|

A framework to foster problem-solving in STEM and computing education

Abstract: Background: Recent developments in STEM and computer science education put a strong emphasis on twenty-first-century skills, such as solving authentic problems. These skills typically transcend single disciplines. Thus, problem-solving must be seen as a multidisciplinary challenge, and the corresponding practices and processes need to be described using an integrated framework. Purpose: We present a fine-grained, integrated, and interdisciplinary framework of problem-solving for education in STEM and computer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 64 publications
(56 reference statements)
1
52
0
2
Order By: Relevance
“…Problem solving plays a central role in STEM education. STEM learning and thinking is usually situated in the context of problem solving (see, for example, Li et al, 2019;Priemer et al, 2019). A view for STEM boundary crossing is to regard the problem-solving process as a boundary object.…”
Section: Problem Solving In Stemmentioning
confidence: 99%
“…Problem solving plays a central role in STEM education. STEM learning and thinking is usually situated in the context of problem solving (see, for example, Li et al, 2019;Priemer et al, 2019). A view for STEM boundary crossing is to regard the problem-solving process as a boundary object.…”
Section: Problem Solving In Stemmentioning
confidence: 99%
“…Recently, Shanta and Wells (2020) found that technology-based learning and engineering design significantly affect students' problem-solving skills. In line with that, Priemer et al (2020) and Lin et al (2015Lin et al ( , 2020 explained that learning by integrating science, technology, engineering, and mathematics can improve student problemsolving. Another report shows that as a type of life skill, student problem-solving can improve in a project-based learning environment (Wurdinger & Qureshi, 2015).…”
Section: Introductionmentioning
confidence: 74%
“…-today is probably the most developed problematics as to online education in general. Since the exact sciences are the most logical and algometric ones, they became natural basis for testing the idea of using online education as a form of providing educational services and a lot of simulators are made all over the world (LeCun, et., 2015); • online education as additional opportunities for secondary and higher education, highly specialized training and retraining programs for adults -based on the position that modern adolescents (the age of middle and high school, as well as students of higher educational institutions) already have collective learning skills and psychologically are more inclined to individual forms of gaining educational services, online education is almost an ideal form of getting knowledge for them (Priemer et al, 2020); • disadvantages of online education, especially for teaching languages and educational and pedagogical work with children of preschool and primary school age who do not have formed habits of learning as a special type of activity -scientific research in this area is carried out both in the area of using online education opportunities by parents for daily developmental activities with the child (to learn colors, songs, new words, tactile exercises, etc. ), as well as many books for children are published that explain to the child in the form of a fairy tale about online space and its place in the modern world (Pinango et al, 2017); • artificial intelligence-based programs for self-education and advanced training online -this area was the first one which gained complete comprehensive AI based programs, that are also certified by states and are actively used in the continuing education and vocational training systems (Norvig & Russel, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%